Strategi Manajemen Akademik Pada Lembaga Pendidikan Tinggi Swasta - Agus Fahmi; Lukmanul Hakim (Universitas Pendidikan Mandalika, 2020)
This study aims to analyze academic management strategies in private higher education institutions. This research method uses a descriptive method with a qualitative approach. Data collection techniques using interviews, observation, and documentation. While the data analysis of this research uses descriptive analysis with an interactive model. The results of this study indicate that the academic management system at tertiary institutions is the core of the implementation of higher education activities that regulate everything including the effectiveness of administration, information, service quality, and efficient use of resources. Management strategy is a process or series of decision-making activities that are fundamental and comprehensive, accompanied by determining how to carry it out, which is made by the leadership and implemented by all levels in an organization to achieve goals. In the implementation of Private Higher Education it is imperative that the quality of academic services be carried out in a directed, disciplined, total quality manner, and ensure the realization of the quality of higher education properly.